PSYCHOLOGICAL SECURITY: ITS IMPORTANCE AND CAUSES IN THE LIGHT OF QURANIC VERSES - Dr. Seyed Zuhair Al-Mesilini (Tunisia) (South Eastern European Journal of Public Health, 2025)
Psychological security is one of the most fundamental human needs, directly influencing the quality of individual and social life. The present study, titled "Psychological Security: Its Importance and Causes in the Light of Quranic Verses," examines the concept of psychological security and the reasons for attaining it from the perspective of the Holy Quran and the traditions of the Prophet Muhammad (peace be upon him). This research emphasizes the importance of the Quran as a comprehensive source for providing sufficient solutions to human challenges, demonstrating that the divine book consistently guarantees security in all dimensions, particularly psychological security. The primary objective of the study is to introduce the concept of psychological security, explain its significance for individuals and society, and explore the role of the Quran in enhancing this security. Additionally, the research seeks to highlight the clear impact of chastity and adherence to divine teachings in establishing and strengthening psychological security. The research methodology includes fundamental approaches for defining concepts, inductive methods for collecting relevant Quranic verses and prophetic traditions, and deductive reasoning to derive the causes and effects of psychological security. The scope of this study involves analyzing Quranic verses related to psychological security, referencing prophetic traditions, and drawing upon the works of righteous predecessors. The findings reveal that the Quran not only provides solutions for worldly and eternal prosperity but also places special emphasis on the psychological dimension of human well-being. Furthermore, this study opens new horizons for future research on psychological security and enriches the Islamic scholarly library.